Political Culture of Madurese Community in Marriage Law: from the Perspective of Utilitarianism and Structuration Theories and Maqasidi Interpretation - Sumarkan, Sumarkan; Choiroh, Ifa Mutitul (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2022)
This research delves into marriage law of Madurese community seen from the purview of its culture and nature. The practice of such marriage contravenes the formal restrictions of the legislation concerning marriage as ruled by the state. Several facts show that some marriage norms were spoiled, sparking the popularity of sirri (unregistered) marriage which further leads to istbat nikah and underage marriage that triggers an exemption. This research employed a qualitative method by garnering information from the judges of a religious court, kiai (a respected and religious Javanese expert in Islam), and the members of the public. The primary data were collected from data on unregistered marriage and exemption in marriage. The data were reductively analyzed, discovering that, first, the political culture of the marriage in Madurese community is captured in a particular pattern: 1) political administration is a measure taken to manipulate the administrative process; 2) political prevention is defined as a legal objective (maslahah, avoiding the likelihood of sharia violations with the basis of hifdz an-nasb) which is a milestone of a legal politics referred to by people, 3) political family and political culture were shaped by the people’s view believing that securing familial relationships from breaking is far more important than what the legislation regulates, 4) political authority represents the presence of a kiai that works like a shield and an escape thoroughfare from the law of the state for the sake of the tradition; second, 1) from the aspect of utilitarianism, there is a point at which political culture of Madurese community and justice meet, 2) the structuration theory views political culture in Madurese community as inevitability, involving religious roles, public, and legal materials, and 3) within maqasidi scope, a law enforcement is seen as preventive (dar’u al-mafasid) as congruent with the aspect of lawmaking objective.